1991
DOI: 10.1002/rcm.1290050507
|View full text |Cite
|
Sign up to set email alerts
|

Collisional spectroscopy approaches in the characterization of 7‐α‐ and 7‐β‐hydroxycholesterol

Abstract: High- and low-energy collision experiments, by means of double-focusing and ion-trap mass spectrometers, respectively, performed on the M+ and [M-H2O]+. ions of 7-alpha- and 7-beta-hydroxycholesterol lead to a clear structural characterization of the two stereoisomers. In particular, the beta isomer shows peculiar fragmentation pathways due to interaction between the hydroxyl group in position 7-beta and the hydrogen atom on C(15).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The ERMS, where the supplementary dipolar r.f. voltage applied to end cap electrodes was varied, has been used to study the binding affinities of noncovalently associated ions and to differentiate structurally isomeric ions 17, 18, 22, 34–43. We have recently reported that one of the projections such as an energy‐resolved projection of ERMS and the parameters obtained from the projection after obtaining regression curves are useful in distinguishing structurally isomeric oligosaccharides 22.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERMS, where the supplementary dipolar r.f. voltage applied to end cap electrodes was varied, has been used to study the binding affinities of noncovalently associated ions and to differentiate structurally isomeric ions 17, 18, 22, 34–43. We have recently reported that one of the projections such as an energy‐resolved projection of ERMS and the parameters obtained from the projection after obtaining regression curves are useful in distinguishing structurally isomeric oligosaccharides 22.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of the ERMS has been recognized and it is applied to investigate the structures of ions and noncovalently associated ions 34–43. Based on our results that ERMS can be analyzed quantitatively,22 we applied the method to a series of trisaccharides consisting of all possible combinations of anomers,33 and describe herein a quantitative analysis of CID spectra, especially energy‐resolved spectra and the relationship between an anomeric configuration and some parameters related to the dissociation energies of individual glycosidic linkages.…”
Section: Introductionmentioning
confidence: 99%
“…Energy-resolved mass spectrometry (ERMS) has been used to investigate the structures of ions and noncovalently associated ions [31][32][33][34][35][36][37][38][39][40]. We have analyzed isomeric oligosaccharides based on ERMS and shown that (1) the primary glycosidic linkage is more stable than the secondary glycoside linkage; and (2) ␣-glyco-␣ sides are more labile than ␤-glycosides, through inves-␤ tigation of malto (␣1¡4)-, ¡ ¡ isomalto (␣1¡6)-, and cello (␤1¡4)-oligosaccharid ¡ ¡ e [26] and trisaccharide libraries with the ␣/␤-Fuc-(1 ␤ ¡6)-␣/␤-Gal-(1 ␤ ¡6)-␣/␤-Glc-octyl ␤ sequence [27].…”
Section: Erms Analysismentioning
confidence: 99%
“…In such cases, a method utilizing quadrupole ion trap mass spectrometry (QIT-MS) is effective. For this reason, QIT-MS has been used to resolve kinetic energy by obtaining a plot of the absolute abundance of precursor and product ions versus the amplitude of radio frequency (rf) applied on end cap electrodes (energy-resolved mass spectrum, ERMS). , Recent advances in QIT-MS equipment allowed us to obtain CID spectra at MS n . We recognized the importance of the ERMS at different stages of MS n for confirming the quantitativeness of the technique, which will be useful for the structural determination of a wide range of isomeric compounds …”
mentioning
confidence: 99%